2014
DOI: 10.2217/whe.14.43
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and Cancer

Abstract: Endometriosis is manifested by the presence of both endometrial glandular and stromal cells outside the uterine cavity. It is characterized by ectopic implantation of endometrial cells with elevated proliferation and migration. Endometriosis is the leading cause of morbidity among premenopausal women and the complex pathogenesis of this disease remains controversial despite extensive research. This rather complex disease has a significant impact on quality of life of many women as none of the current treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 52 publications
(62 reference statements)
0
34
0
1
Order By: Relevance
“…These alterations are summarized in Table 4. Although endometriosis is considered a ‘benign’ disease, it resembles the biologic behavior of malignant cells [113,114], and a change in the expression of various junctional proteins may support the invasive properties of this tissue and may facilitate its growth at ectopic localizations. Moreover, these impairments may also contribute to endometriosis-associated infertility.…”
Section: Direct Cell–cell Interactions In Endometrial Pathophysiologymentioning
confidence: 99%
“…These alterations are summarized in Table 4. Although endometriosis is considered a ‘benign’ disease, it resembles the biologic behavior of malignant cells [113,114], and a change in the expression of various junctional proteins may support the invasive properties of this tissue and may facilitate its growth at ectopic localizations. Moreover, these impairments may also contribute to endometriosis-associated infertility.…”
Section: Direct Cell–cell Interactions In Endometrial Pathophysiologymentioning
confidence: 99%
“…Typically, malignant transformation of endometriosis may result in endometrioid adenocarcinoma and clear cell carcinoma, as well as, Müllerian-type mucinous and serous borderline tumors, and adenosarcoma and endometrial stromal sarcoma [63]. Available epidemiological studies also indicated that women with endometriosis may be at a higher risk of extra-ovarian cancers, for example, non-Hodgkin's lymphoma, brain tumors, endocrine cancer, breast cancers, and cutaneous melanoma [65][66][67][68]. Figures 4 and 5 summarize the estimated effect sizes reported in various studies on association between endometriosis and ovarian or extra-ovarian cancers.…”
Section: Endometriosis-associated Cancersmentioning
confidence: 99%
“…It is a high MW glycoprotein originally used as a tumor marker for ovarian tumors (Bast et al, 1981). Its use in endometriosis is based on a well-established connection between endometriosis and ovarian cancer (Kralickova et al, 2014). However, it is important to remember that it cannot be used for differential diagnosis between endometriosis and cancer, as the level is increased in patients with both endometriosis and cancer (Lenhard et al, 2009).…”
Section: Tumor Markers Ca125 and Ca19-9mentioning
confidence: 99%